Public Procurement Rules and the Prevention of Corruption - Papierz, Julia (Zasady zamówień publicznych a zapobieganie korupcji, 2024)
The article points out the difficulties of defining the phenomenon of corruption, the main risks of public procurement related to the occurrence of corrupt behaviour, and the role of the proper application of public procurement rules as tools for the prevention of corruption. This is because these principles are a guide for the contracting authority on how to take certain actions during the procedure, and which ones to avoid in order to ensure that the public procurement procedure is carried out in a lawful manner and that public funds are spent in an efficient and reasonable manner. Where discretionary slack exists, this is an indicator of the proper use of the discretion left to the contracting authority. The risk of corruption in public procurement is mainly due to the fact that significant public funds are spent in the course of public procurement, and the risk of bribery or collusion in tendering exists, regardless of the stage of the procedure.
Ekonomia XXI Wieku = Economics of the 21st Century, 2024, Nr 27, s. 10-19
Keywords: public procurement; corruption; principle of fair competition; principle of transparency; principle of openness; principle of writtenness; zamówienia publiczne; korupcja; zasady uczciwej konkurencji; zasada przejrzystości; zasada jawności; zasada pisemności